Conjunctival infiltrates and cytokines in an experimental immune-mediated blepharoconjunctivitis rat model - Aihua Hou; Aihua Hou; Min Qi Tin; Beau Fenner; Beau Fenner; Yu-Chi Liu; Yu-Chi Liu; Louis Tong; Louis Tong; Louis Tong; Louis Tong (Frontiers in Medicine, 2023)
PurposeTo characterize the histopathological and immunological findings of a rat model of allergic blepharoconjunctivitis (BC) and demonstrate its potential utility for the assessment of BC therapies.MethodsSprague–Dawley (SD) rats were immunized with ovalbumin (OVA) and topically challenged with OVA (BC group) or PBS (control group), while a corticosteroid group was pre-treated with triamcinolone acetate 24 h before the challenge. Morphological features were evaluated and tissues were harvested for histological, flow cytometry and cytokine analysis.ResultsThe BC group rats developed eyelid excoriations, redness, and conjunctival edema 24 h after the OVA challenge, while corticosteroid pre-treated and PBS-challenged rats were unaffected. The BC features were reduced despite repeated challenges for 5 days. Massive immune cell infiltration was observed in conjunctivae of BC rats, while no significant infiltration was seen in the other groups. Populations of T cells, mono-macrophages, neutrophils, and NK cells made up more than 77% of CD45+7AAD− cells in the conjunctival tissues. T cell proportions were increased at 96 h compared to 24 h post-challenge, while macrophages decreased during the same time period. Eosinophils and intraepithelial neutrophils were detected in the BC rats, but not in the PBS and corticosteroid groups. BC eyes had significantly higher levels of IFN-γ and IL-2, while IL-4 and IL-6 levels were similar to controls.ConclusionA robust BC response was detected in this rat model which was suppressed by corticosteroid pre-treatment. Immune cell composition and cytokine profiles changed over time.